diff options
Diffstat (limited to 'Master/texmf-dist/doc/latex/mil3/multline.tpl')
-rw-r--r-- | Master/texmf-dist/doc/latex/mil3/multline.tpl | 495 |
1 files changed, 0 insertions, 495 deletions
diff --git a/Master/texmf-dist/doc/latex/mil3/multline.tpl b/Master/texmf-dist/doc/latex/mil3/multline.tpl deleted file mode 100644 index 09ad30d23bc..00000000000 --- a/Master/texmf-dist/doc/latex/mil3/multline.tpl +++ /dev/null @@ -1,495 +0,0 @@ -% Sample file: multline.tpl -% multiline math formula template file - - -% Section 5.2 Gathering formulas - -\begin{gather} - x_{1} x_{2} + x_{1}^{2} x_{2}^{2} + x_{3}, \label{E:mm1.1}\\ - x_{1} x_{3} + x_{1}^{2} x_{3}^{2} + x_{2}, \label{E:mm1.2}\\ - x_{1} x_{2} x_{3}. \label{E:mm1.3} -\end{gather} - -% 5.3 Splitting a long formula - -\begin{multline}\label{E:mm2} - (x_{1} x_{2} x_{3} x_{4} x_{5} x_{6})^{2}\\ - + (y_{1} y_{2} y_{3} y_{4} y_{5} +y_{1} y_{3} y_{4} y_{5} y_{6} - + y_{1} y_{2} y_{4} y_{5} y_{6} - + y_{1} y_{2} y_{3} y_{5} y_{6})^{2}\\ - + (z_{1} z_{2} z_{3} z_{4} z_{5} +z_{1} z_{3} z_{4} z_{5} z_{6} - + z_{1} z_{2} z_{4} z_{5} z_{6} - + z_{1} z_{2} z_{3} z_{5} z_{6})^{2}\\ - + (u_{1} u_{2} u_{3} u_{4} + u_{1} u_{2} u_{3} u_{5} + - u_{1} u_{2} u_{4} u_{5} + u_{1} u_{3} u_{4} u_{5})^{2} -\end{multline} - -\begin{multline*} - (x_{1} x_{2} x_{3} x_{4} x_{5} x_{6})^{2}\\ - + (x_{1} x_{2} x_{3} x_{4} x_{5} - + x_{1} x_{3} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{3} x_{5} x_{6})^{2}\\ - + (x_{1} x_{2} x_{3} x_{4} + x_{1} x_{2} x_{3} x_{5} - + x_{1} x_{2} x_{4} x_{5} + x_{1} x_{3} x_{4} x_{5})^{2} -\end{multline*} -\begin{setlength}{\multlinegap}{0pt} - \begin{multline*} - (x_{1} x_{2} x_{3} x_{4} x_{5} x_{6})^{2}\\ - + (x_{1} x_{2} x_{3} x_{4} x_{5} - + x_{1} x_{3} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{3} x_{5} x_{6})^{2}\\ - + (x_{1} x_{2} x_{3} x_{4} + x_{1} x_{2} x_{3} x_{5} - + x_{1} x_{2} x_{4} x_{5} + x_{1} x_{3} x_{4} x_{5})^{2} - \end{multline*} -\end{setlength} - -\begin{multline*} - (x_{1} x_{2} x_{3} x_{4} x_{5} x_{6})^{2}\\ - \shoveleft{+ (x_{1} x_{2} x_{3} x_{4} x_{5} - + x_{1} x_{3} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{3} x_{5} x_{6})^{2}}\\ - + (x_{1} x_{2} x_{3} x_{4} + x_{1} x_{2} x_{3} x_{5} - + x_{1} x_{2} x_{4} x_{5} + x_{1} x_{3} x_{4} x_{5})^{2} -\end{multline*} - -% 5.4.3 Group numbering - -\begin{gather} - x_{1} x_{2} + x_{1}^{2} x_{2}^{2} + x_{3},\label{E:mm1} \\ - x_{1} x_{3} + x_{1}^{2} x_{3}^{2} + x_{2},\tag{\ref{E:mm1}a}\\ - x_{1} x_{2} x_{3};\tag{\ref{E:mm1}b} -\end{gather} - -\begin{subequations}\label{E:gp} - \begin{gather} - x_{1} x_{2} + x_{1}^{2} x_{2}^{2} + x_{3},\label{E:gp1}\\ - x_{1} x_{3} + x_{1}^{2} x_{3}^{2} + x_{2},\label{E:gp2}\\ - x_{1} x_{2} x_{3},\label{E:gp3} - \end{gather} -\end{subequations} - - % 5.5 Aligned columns - -\begin{align}\label{E:mm3} - f(x) &= x + yz & g(x) &= x + y + z\\ - h(x) &= xy + xz + yz & k(x) &= (x + y)(x + z)(y + z) - \notag -\end{align} - -% 5.5.1 An align variant - -\begin{flalign}\label{E:mm3fl} - f(x) &= x + yz & g(x) &= x + y + z\\ - h(x) &= xy + xz + yz & k(x) &= (x + y)(x + z)(y + z) - \notag -\end{flalign} - -% 5.5.2 eqnarray, the ancestor of align - -\begin{eqnarray} - x & = & 17y \\ - y & > & a + b + c -\end{eqnarray} - -\begin{align} - x & = 17y \\ - y & > a + b + c -\end{align} - -% 5.5.3 The subformula rule revisited - -\begin{align} - x_{1} + y_{1} + \left( \sum_{i < 5} \binom{5}{i} - &+ a^{2} \right)^{2}\\ - \left( \sum_{i < 5} \binom{5}{i} + \alpha^{2} \right)^{2} -\end{align} - -\begin{align*} - &x_{1} + y_{1} + \left( \sum_{i < 5} \binom{5}{i} - + a^{2} \right)^{2}\\ - &\phantom{x_{1} + y_{1} + {}} - \left( \sum_{i < 5} \binom{5}{i} + \alpha^{2} \right)^{2} -\end{align*} - -% 5.5.4 The alignat environment - -\begin{alignat}{2}\label{E:mm3A} - f(x) &= x + yz & g(x) &= x + y + z\\ - h(x) &= xy + xz + yz & k(x) &= (x + y)(x + z)(y + z) - \notag -\end{alignat} - -\begin{alignat}{2}\label{E:mm3B} - f(x) &= x + yz & g(x) &= x + y + z\\ - h(x) &= xy + xz + yz \qquad & k(x) &= (x + y)(x + z)(y + z) - \notag - -\begin{alignat}{2}\label{E:mm4} - x &= x \wedge (y \vee z) & &\quad\text{(by distributivity)}\\ - &= (x \wedge y) \vee (x \wedge z) & & - \quad\text{(by condition (M))}\notag\\ - &= y \vee z \notag -\end{alignat} - -\begin{alignat}{2} - (A + B C)x &+{} &C &y = 0,\\ - Ex &+{} &(F + G)&y = 23. -\end{alignat} - -\begin{alignat}{4} - a_{11}x_1 &+ a_{12}x_2 &&+ a_{13}x_3 && &&= y_1,\\ - a_{21}x_1 &+ a_{22}x_2 && &&+ a_{24}x_4 &&= y_2,\\ - a_{31}x_1 & &&+ a_{33}x_3 &&+ a_{34}x_4 &&= y_3. -\end{alignat} - -% 5.5.5 Intertext - -\begin{align}\label{E:mm5} - h(x) &= \int \left( - \frac{ f(x) + g(x) } - {1 + f^{2}(x)} + - \frac{1 + f(x)g(x)} - { \sqrt{1 - \sin x} } - \right) \, dx\\ - \intertext{The reader may find the following form easier to - read:} - &= \int \frac{1 + f(x)} - {1 + g(x)} - \, dx - 2 \arctan(x - 2) \notag -\end{align} - -\begin{align*} - f(x) &= x + yz & \qquad g(x) &= x + y + z \\ - \intertext{The reader also may find the following - polynomials useful:} - h(x) &= xy + xz + yz - & \qquad k(x) &= (x + y)(x + z)(y + z) -\end{align*} - -% 5.6 Aligned subsidiary math environments - -% 5.6.1 Subsidiary variants of aligned math environments - -\[ - \begin{aligned} - x &= 3 + \mathbf{p} + \alpha \\ - y &= 4 + \mathbf{q}\\ - z &= 5 + \mathbf{r} \\ - u &=6 + \mathbf{s} - \end{aligned} - \text{\qquad using\qquad} - \begin{gathered} - \mathbf{p} = 5 + a + \alpha \\ - \mathbf{q} = 12 \\ - \mathbf{r} = 13 \\ - \mathbf{s} = 11 + d - \end{gathered} -\] - -\begin{align}\label{E:mm5} - h(x) &= \int \left( - \frac{ f(x) + g(x) } - {1 + f^{2}(x)} + - \frac{1 + f(x)g(x)} - { \sqrt{1 - \sin x} } - \right) \, dx\\ - \intertext{The reader may find the following form easier to - read:} - &= \int \frac{1 + f(x)} - {1 + g(x)} - \, dx - 2 \arctan(x - 2) \notag -\end{align} - -\begin{equation}\label{E:mm6} - \begin{aligned} - h(x) &= \int \left( - \frac{ f(x) + g(x) } - { 1 + f^{2}(x) } + - \frac{ 1 + f(x)g(x) } - { \sqrt{1 - \sin x} } - \right) \, dx\\ - &= \int \frac{ 1 + f(x) } - { 1 + g(x) } \, dx - 2 \arctan (x - 2) - \end{aligned} -\end{equation} - -\[ - \begin{aligned}[b] - x &= 3 + \mathbf{p} + \alpha \\ - y &= 4 + \mathbf{q}\\ - z &= 5 + \mathbf{r} \\ - u &=6 + \mathbf{s} - \end{aligned} - \text{\qquad using\qquad} - \begin{gathered}[b] - \mathbf{p} = 5 + a + \alpha \\ - \mathbf{q} = 12 \\ - \mathbf{r} = 13 \\ - \mathbf{s} = 11 + d - \end{gathered} -\] - -% 5.6.2 Split - -\begin{equation}\label{E:mm7} - \begin{split} - (x_{1}x_{2}&x_{3}x_{4}x_{5}x_{6})^{2}\\ - &+ (x_{1}x_{2}x_{3}x_{4}x_{5} - + x_{1}x_{3}x_{4}x_{5}x_{6} - + x_{1}x_{2}x_{4}x_{5}x_{6} - + x_{1}x_{2}x_{3}x_{5}x_{6})^{2} - \end{split} -\end{equation} - -\begin{align}\label{E:mm8} - \begin{split} - f &= (x_{1} x_{2} x_{3} x_{4} x_{5} x_{6})^{2}\\ - &= (x_{1} x_{2} x_{3} x_{4} x_{5} - + x_{1} x_{3} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{3} x_{5} x_{6})^{2}, - \end{split}\\ - g &= y_{1} y_{2} y_{3}.\label{E:mm9} -\end{align} - -\begin{gather}\label{E:mm10} - \begin{split} - f &= (x_{1} x_{2} x_{3} x_{4} x_{5} x_{6})^{2}\\ - &= (x_{1} x_{2} x_{3} x_{4} x_{5} - + x_{1} x_{3} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{4} x_{5} x_{6} - + x_{1} x_{2} x_{3} x_{5} x_{6})^{2}\\ - &= (x_{1} x_{2} x_{3} x_{4} - + x_{1} x_{2} x_{3} x_{5} - + x_{1} x_{2} x_{4} x_{5} - + x_{1} x_{3} x_{4} x_{5})^{2} - \end{split}\\ - \begin{align*} - g &= y_{1} y_{2} y_{3}\\ - h &= z_{1}^{2} z_{2}^{2} z_{3}^{2} z_{4}^{2} - \end{align*} -\end{gather} - -% 5.7 Adjusted columns - -\begin{equation*} - \left( - \begin{matrix} - a + b + c & uv & x - y & 27\\ - a + b & u + v & z & 1340 - \end{matrix} - \right) = - \left( - \begin{matrix} - 1 & 100 & 115 & 27\\ - 201 & 0 & 1 & 1340 - \end{matrix} - \right) -\end{equation*} - -\begin{equation*} - \left( - \begin{array}{cccr} - a + b + c & uv & x - y & 27\\ - a + b & u + v & z & 1340 - \end{array} - \right) = - \left( - \begin{array}{rrrr} - 1 & 100 & 115 & 27\\ - 201 & 0 & 1 & 1340 - \end{array} - \right) -\end{equation*} - -\begin{equation}\label{E:mm11} - f(x) = - \begin{cases} - -x^{2}, &\text{\CMR if $x < 0$;} \\ - \alpha + x, &\text{\CMR if $ 0 \leq x \leq 1$;}\\ - x^{2}, &\text{\CMR otherwise.} - \end{cases} -\end{equation} - -% 5.7.1 Matrices - -\begin{equation*} - \left( - \begin{matrix} - a + b + c & uv & x - y & 27 \\ - a + b & u + v & z & 1340 - \end{matrix} - \right) = - \left( - \begin{matrix} - 1 & 100 & 115 & 27 \\ - 201 & 0 & 1 & 1340 - \end{matrix} - \right) -\end{equation*} - -\begin{matrix} - a + b + c & uv & x - y & 27 \\ - a + b & u + v & z & 134 -\end{matrix} - -\begin{equation}\label{E:mm12} - \setcounter{MaxMatrixCols}{12} - \begin{matrix} - 1 & 2 & 3 & 4 & 5 & 6 & 7 & 8 & 9 & 10 & 11 & 12\\ - 1 & 2 & 3 & \hdotsfor{7} & 11 & 12 - \end{matrix} -\end{equation} - -\begin{equation}\label{E:mm12dupl} - \setcounter{MaxMatrixCols}{12} - \begin{matrix} - 1 & 2 & 3 & 4 & 5 & 6 & 7 & 8 & 9 & 10 & 11 & 12\\ - 1 & 2 & 3 & \hdotsfor[3]{7} & 11 & 12 - \end{matrix} -\end{equation} - -% Matrix variants - -\begin{alignat*}{3} - &\ - \begin{matrix} - a + b + c & uv\\ - a + b & c + d - \end{matrix} - \qquad - & & - \begin{pmatrix} - a + b + c & uv\\ - a + b & c + d - \end{pmatrix} - \qquad - & & - \begin{bmatrix} - a + b + c & uv\\ - a + b & c + d - \end{bmatrix} - \\ - & - \begin{vmatrix} - a + b + c & uv\\ - a + b & c + d - \end{vmatrix} - \qquad - & & - \begin{Vmatrix} - a + b + c & uv\\ - a + b & c + d - \end{Vmatrix} - \qquad - & & - \begin{Bmatrix} - a + b + c & uv\\ - a + b & c + d - \end{Bmatrix} -\end{alignat*} - -\begin{equation*} - \left( - \begin{matrix} - 1 & 0 & \dots & 0 \\ - 0 & 1 & \dots & 0 \\ - \vdots & \vdots & \ddots & \vdots\\ - 0 & 0 & \dots & 1 - \end{matrix} - \right] -\end{equation*} -\end{verbatim} -which produces -\begin{equation*} - \left( - \begin{matrix} - 1 & 0 & \dots & 0 \\ - 0 & 1 & \dots & 0 \\ - \vdots & \vdots & \ddots & \vdots\\ - 0 & 0 & \dots & 1 - \end{matrix} - \right] -\end{equation*} - -% Small matrix - -$\begin{pmatrix} - a + b + c & uv\\ - a + b & c + d -\end{pmatrix}$ - -$\left( -\begin{smallmatrix} - a + b + c & uv \\ - a + b & c + d -\end{smallmatrix} -\right)$ - -% 5.7.2 Arrays - -\begin{equation*} - \left( - \begin{array}{cccc} - a + b + c & uv & x - y & 27 \\ - a + b & u + v & z & 134 - \end{array} - \right) -\end{equation*} - -% 5.7.3 Cases - -\begin{equation} - f(x)= - \begin{cases} - -x^{2}, &\text{if $x < 0$;}\\ - \alpha + x, &\text{if $0 \leq x \leq 1$;}\\ - x^{2}, &\text{otherwise.} - \end{cases} -\end{equation} - -% 5.8 Commutative diagrams - -\[ - \begin{CD} - A @>>> B \\ - @VVV @VVV\\ - C @= D - \end{CD} -\] - -\[ - \begin{CD} - \mathbb{C} @>H_{1}>> \mathbb{C} @>H_{2}>> \mathbb{C} \\ - @VP_{c,3}VV @VP_{\bar{c},3}VV @VVP_{-c,3}V \\ - \mathbb{C} @>H_{1}>> \mathbb{C} @>H_{2}>> \mathbb{C} - \end{CD} -\] - -\[ - \begin{CD} - A @>\log>> B @>>\text{bottom}> C - @= D @<<< E - @<<< F\\ - @V\text{one-one}VV @. @AA\text{onto}A @|\\ - X @= Y @>>> Z - @>>> U\\ - @A\beta AA @AA\gamma A @VVV @VVV\\ - D @>\alpha>> E @>>> H - @. I\\ - \end{CD} -\] - -% 5.9 Pagebreak - -{\allowdisplaybreaks -\begin{align}\label{E:mm13} - a &= b + c,\\ - d &= e + f,\\ - x &= y + z,\\ - u &= v + w. -\end{align} -}% end of \allowdisplaybreaks |